Immune Response and Apoptosis-Related Pathways Induced by Aeromonas schubertii Infection of Hybrid Snakehead (Channa maculata♀ × Channa argus♂) - Chun Liu; Jie Ma; Defeng Zhang; Wei Li; Biao Jiang; Zhendong Qin; Youlu Su; Li Lin; Qing Wang (Pathogens, 2021)
Aeromonas schubertii is the etiological pathogen of internal organ nodules in snakehead fish. Infections with A. schubertii produce a significant economic loss in aquaculture. Therefore, it is important to examine the immune mechanisms by which snakeheads defend against A. schubertii infection. In this study, we established a hybrid snakehead infection model by intraperitoneal injection of A. schubertii that produced internal organ nodules. The splenic immune response of infected fish was examined at the transcriptome level by Illumina-seq analysis. Results showed 14,796 differentially expressed genes (DEGs) following A. schubertii infection, including 4441 up-regulated unigenes and 10,355 down-regulated unigenes. KEGG analysis showed 2084 DEGs to be involved in 192 pathways, 14 of which were immune-related. Twelve DEGs were used to validate quantitative real-time PCR results with RNA-seq data. Time-course expression analysis of six genes demonstrated modulation of the snakehead immune response by A. schubertii. Furthermore, transcriptome analysis identified a substantial number of DEGs that were involved in the apoptosis signaling pathway. TUNEL analysis of infected spleens confirmed the presence of apoptotic cells. This study provided new information for a further understanding of the pathogenesis of A. schubertii in snakeheads, which can be used to prevent and possibly treat A. schubertii infections.